Safer Cycling Advocate Program. Best Practice Guide. - Woolsgrove, Ceri; Armstrong, James (My University, 2020)
The Safer Cycling Advocate Program (SCAP) seeks to empower civil society organizations by building their capacity to advocate for safer roads and to promote cycling as a transport mode. According to the World Resource Institute research study “Saving lives with sustainable transport”, when there is a shift towards cycling in cities on a larger scale, safety trends improve considerably and not only for non-motorized modes. As an example, Copenhagen is cited as a city where infrastructure improvements to encourage cycling had as a direct consequence a sharp decrease on road fatalities5. Road Safety measures should also seek to increase cycling and other sustainable modes of transport, promoting their use through comfortable, and easy to use infrastructure. The Safer Cycling Advocate Program’s Best Practice Guide contains a list of positive measures that can be adopted to promote cycling and cycling safety. It is based on the experiences of the Netherlands and Denmark, two countries that have developed significant expertise in the field of cycling safety.
Keywords: Verkehrssicherheit; Anwendungspraxis; Fahrradverkehr; Infrastruktur; Verkehrsverhalten; Ratgeber; Nachhaltige Verkehrsentwicklung